Stock Market Performance and Economic Growth: Evidence from Nigeria Employing Vector Error Correction Model Framework - Anigbogu, Ugochukwu E; Nduka, Eleanya K (The Economics and Finance Letters, 2014)
This study examines the long-run and causal relationship between stock market performance and economic growth in Nigeria for the period from 1987Q1 to 2012Q4 ¬inclusive. The study employs the Augmented-Dickey Fuller test for unit root, the Johansen (1995) Maximum Likelihood cointegration technique and Vector Error Correction Model framework to capture long-run and short-run relationships in the cointegrating vectors of Nigerian stock market and economic growth. The study further employs Granger (1969) Causality, Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) to capture shocks transmission and AR root graph for stability. The optimum lag length was selected based on the Schwartz and Hannan-Quin information criteria. The results of the cointegration test confirm that there exists a long-run relationship between stock market performance and economic growth, while the causality test results suggest that stock market performance causes economic growth with feedback. The Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) suggest that shocks from the stock market do not impede economic growth. Furthermore, the result of the AR root graph indicates that the Nigerian stock exchange market is not stable. Hence, the current reforms and policies going on in the Nigerian stock exchange should be sustained to boost investors’ confidence and participation.